Palestinsko-izraelski konflikt - Tekavčič Veber, Maruša (Teorija in praksa, 2024)
The Palestinian-Israeli conflict raises several pertinent international legal questions that are analysed in the paper from the perspective of the right of peoples to self-determination, the prohibition of the use of force (jus ad bellum), the law of armed conflict (jus in bello), rules governing individual criminal responsibility and state responsibility (jus post bellum), and rules governing obligations of the international community. Understanding these areas of law is essential for determining the potential responsibility of the various actors involved and simultaneously also discloses two aspects of modern international law. On one hand, situations of the use of force by non-state actors require careful analysis and raise a number of questions to which "state sovereignty-centred" international law provides no clear-cut answers. On the other hand, deriving from the erga omnes (partes) nature of some obligations, there is growing recognition that all states in the international community are entitled to respond and invoke the responsibility of wrongdoing states in such situations. The paper concludes, however, that in the absence of political will, the selectivity of implementation remains a fundamental weakness of international law.
Keywords: Arabsko-izraelski spor; erga omnes (partes); international law of armed conflict; Judovsko-arabski odnosi; Mednarodni odnosi; Mednarodno pravo; mednarodno pravo oboroženih spopadov; nedržavni akterji; non-state actors; odgovornost; Palestina; Palestine; pravica do samoobrambe; pravica narodov do samoodločbe; responsibility; the right of peoples to self-determination; the right of self-defence